Pengaruh Bentuk Pola Persebaran Permukiman Penduduk terhadap RTH di Kampung Tua Tanjung Riau - Aguspriyanti, Carissa Dinar; Shevriyanto, Billy; Charlie, Charlie (Institut Teknologi Adhi Tama Surabaya, 2021)
Abstract. The undirected distribution pattern of settlements tends to cause irregular building arrangement patterns. Coupled with the increasing building density level, the availability of open space is at risk of decreasing. The coastal settlement of Kampung Tua Tanjung Riau in Batam is a vivid example of this kind of settlements development issue. Through descriptive-qualitative research methods, the form of distribution pattern of settlements was observed from the street layout and buildings location. Subsequently, it can be identified and analysed that the longitudinal distribution pattern of settlements in Kampung Tua Tanjung Riau affects the availability of green open space in the area which is considered inadequate. This research is expected to be taken into consideration by related agencies including the government in overcoming the existing problems in Kampung Tua Tanjung Riau.Keywords: Distribution Pattern of Settlements, Green Open Space, Kampung Tua Tanjung RiauÂ Abstrak. Bentuk pola persebaran permukiman penduduk yang tidak terarah cenderung menyebabkan ketidakteraturan pola penataan bangunan. Ditambah dengan tingkat kepadatan yang semakin meningkat, ketersediaan ruang terbuka beresiko menurun. Permukiman pesisir Kampung Tua Tanjung Riau di Kota Batam, merupakan salah satu contoh nyata permasalahan perkembangan permukiman tersebut. Melalui metode penelitian kualitatif deskriptif, bentuk pola persebaran permukiman ditinjau dari pola jalan dan lokasi hunian. Kemudian, dapat diidentifikasi dan dianalisis bahwa bentuk pola persebaran permukiman yang memanjang di Kampung Tua Tanjung Riau mempengaruhi ketersediaan RTH (Ruang Terbuka Hijau) di kawasan tersebut yang notabene dinilai masih kurang memadai. Penelitian ini diharapkan dapat menjadi bahan pertimbangan instansi terkait termasuk pemerintah dalam mengatasi permasalahan yang ada di kawasan Kampung Tua Tanjung Riau.Kata Kunci: Pola Persebaran Permukiman, Ruang Terbuka Hijau, Kampung Tua Tanjung Riau